'Dear Netflix…': Informal local intermediaries on the periphery of the global VOD market. Issue 3 (1st October 2020) - Szczepanik, Petr
Academic discussion of Netflix has already highlighted the labour of localization that the global service has had to carry out or contract in order to operate smoothly across borders. But not much has been said about independent local players who help to align the service with local audiences, doing so often without any authorization or recognition, and who are still looking for a place in the new distribution ecosystem. Employing the perspective of valuation studies, this article discusses the changing business model of a Czech video-on-demand (VOD) directory, Filmtoro, as an example of a new type of local intermediary contributing to the social construction of the global VOD market.